Tuesday

March 3, 2015

March 3, 2015

Posted by **Tanya** on Wednesday, May 1, 2013 at 7:46pm.

f(3) − g(3)

- Algebra -
**Reiny**, Wednesday, May 1, 2013 at 8:17pmf(3) - g(3)

= 2(3^2) - 1 - (-2(3) + 1)

= 18-1 - (-5)

= 23

**Answer this Question**

**Related Questions**

Algebra - Given f(x)=2x^2 + 9x − 7and g(x)=2x −6, find the following...

biology - Given the part of the molecule shown below, can the underlined atom ...

Alg - Given f(x) = 2x^2 – 2 and g(x) = –2x + 4, find the following. (f − g...

algebra - Which of the following is equivalent to the expression (t2 − t...

Algebra - Please help I can't figure out these two. Express f(x) in the form a(x...

Grade 12 Calculus - Evaluate each of the following. Show all your calculations...

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

Alg. - Given g(x) = x^2 – 3, find the following. g(−4 + h) − g(&#...

Algebra - Which of the following equations containing grouping symbols is ...